The use of complementary and alternative medicine during pregnancy: a cross-sectional study from Palestine - Yara Quzmar; Zeina Istiatieh; Hala Nabulsi; Sa'ed H. Zyoud; Samah W. Al-Jabi (BMC, 2021)
Abstract Background The use of complementary and alternative medicine (CAM) is increasing worldwide. To the best of knowledge, there is a lack of studies that assess CAM use by Palestinian women during pregnancy. This research aims to determine the prevalence of Palestinian women's use of CAM during pregnancy, the most frequently used CAM products during the pregnancy period, the main sources that encourage the use of CAM among pregnant women, and the causes of CAM use. Methods A descriptive, cross-sectional study was conducted in Palestine using a questionnaire from April 2018 to March 2019. The samples were selected by convenience sampling, including currently pregnant or previously pregnant women in the Obstetrics and Gynecology (OBGYN) clinic at Rafedia Hospital and in primary health care clinics in Nablus city-Palestine. The questionnaire covered socio-demographic variables, health status, types and frequency of CAM used, patients' sources of information, causes of their usage, attitudes, and beliefs. Results Four hundred currently or previously pregnant women participated. Three hundred fifty-five (91.5%) used at least one method of CAM during pregnancy. Most women used at least one method of biologically-based therapies during pregnancy (87.7%). One hundred and one pregnant women (26.7%) utilised at least one type of herb during pregnancy. The most-reported herb used by 12.3% of participants was anise. Of the mind-body therapies, prayer was the most commonly used method during pregnancy (8.3%). Two hundred and sixty-one (65.3%) participants used CAM because they believed CAM was not harmful to them or their babies during pregnancy. Participants gained most of their information about CAM from their families (43.8%) and friends (24.3%). Approximately two-thirds of participants (64.0%) thought that obstetricians should be able to advise on commonly used CAM. Conclusions During pregnancy, CAM products are commonly used, and it is important to determine what types are being used by women in Palestine. These findings supplement the body of knowledge on the use of CAM by pregnant women. Pregnancy care providers need to be aware to the familiar types of CAM that women use.